2000
DOI: 10.1007/s002210000530
|View full text |Cite
|
Sign up to set email alerts
|

A repetitive intracortical microstimulation pattern induces long-lasting synaptic depression in brain slices of the rat primary somatosensory cortex

Abstract: Repetitive intracortical microstimulation (ICMS) applied to the rat primary somatosensory cortex (SI) in vivo was reported to induce reorganization of receptive fields and cortical maps. The present study was designed to examine the effect of such an ICMS pattern applied to layer IV of brain slices containing SI on the efficacy of synaptic input to layer II/III. Effects of ICMS on the synaptic strength was quantified for the first synaptic component (s1) of cortical field potentials (FPs) recorded from layer I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…The ICMS protocol differs from conventional methods of low-or high-frequency stimulation to induce synaptic plasticity such as long-term potentiation (LTP) or long-term depression (LTD). When we used a slice preparation of adult rat somatosensory cortex, we found that ICMS close to the stimulation site evoked a depression of local field potentials, implying a distinct form of synaptic depression of excitatory mechanisms (32).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The ICMS protocol differs from conventional methods of low-or high-frequency stimulation to induce synaptic plasticity such as long-term potentiation (LTP) or long-term depression (LTD). When we used a slice preparation of adult rat somatosensory cortex, we found that ICMS close to the stimulation site evoked a depression of local field potentials, implying a distinct form of synaptic depression of excitatory mechanisms (32).…”
Section: Discussionmentioning
confidence: 92%
“…The resulting temporally synchronized neuronal discharges are highly effective for the induction of reorganizational processes. ICMS has been used successfully to study rapid, i.e., plastic changes inducible within a few hours in adult motor, somatosensory, and auditory cortex and thalamus; these changes were fully reversible (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The region of tissue that is stimulated by direct activation during ICMS is very small (50-100 m; refs.…”
mentioning
confidence: 99%
“…The increase of inhibition adjusts the excitatory output of pyramidal cells and consolidates plasticity during the critical period (Morishita and Hensch, 2008). In a previous study, it was shown that repetitive intracortical microstimulation in brain slices of the rat SI induces long-term depression in the excitatory system (Heusler et al, 2000). As a consequence, the transmitter release of the depressed excitatory synapses is reduced.…”
Section: Suppression Zonementioning
confidence: 99%
“…1B). It has been demonstrated that the early negativity is a pre-synaptic volley, while the late components belong to postsynaptic potentials [38] .…”
Section: Spatial Map Of Neural Circuit In the Hindlimb Represen-mentioning
confidence: 99%
“…However, LTP induced in the neocortex is proven to be related with CS parameter. For example, the optimal form of CS to induce LTP in rat S1 cortex slice is suggested to be high frequency stimulation (HFS), rather than low frequency or theta burst stimulation [38] .…”
Section: Spatial Map Of Neural Circuit In the Hindlimb Represen-mentioning
confidence: 99%